Identification of functional rare coding variants in IGF-1 gene in humans with exceptional longevity - Amanat Ali; Zhengdong D. Zhang; Tina Gao; Sandra Aleksic; Evripidis Gavathiotis; Nir Barzilai; Sofiya Milman (Scientific Reports)
Abstract Diminished signaling via insulin/insulin-like growth factor-1 (IGF-1) axis is associated with longevity in different model organisms. IGF-1 gene is highly conserved across species, with only few evolutionary changes identified in it. Despite its potential role in regulating lifespan, no coding variants in IGF-1 have been reported in human longevity cohorts to date. This study investigated the whole exome sequencing data from 2,108 individuals in a cohort of Ashkenazi Jewish centenarians, their offspring, and controls without familial longevity to identify functional IGF-1 coding variants. We identified two likely functional coding variants IGF-1:p.Ile91Leu and IGF-1:p.Ala118Thr in our longevity cohort. Notably, a centenarian specific novel variant IGF-1:p.Ile91Leu was located at the binding interface of IGF-1–IGF-1R, whereas IGF-1:p.Ala118Thr was significantly associated with lower circulating levels of IGF-1. We performed extended all-atom molecular dynamics simulations to evaluate the impact of Ile91Leu on stability, binding dynamics and energetics of IGF-1 bound to IGF-1R. The IGF-1:p.Ile91Leu formed less stable interactions with IGF-1R’s critical binding pocket residues and demonstrated lower binding affinity at the extracellular binding site compared to wild-type IGF-1. Our findings suggest that IGF-1:p.Ile91Leu and IGF-1:p.Ala118Thr variants attenuate IGF-1R activity by impairing IGF-1 binding and diminishing the circulatory levels of IGF-1, respectively. Consequently, diminished IGF-1 signaling resulting from these variants may contribute to exceptional longevity in humans.